Avoidant personality disorder as a social anxiety phenotype: risk factors, associations and treatment. Issue 1 (January 2016) - Lampe, Lisa
Abstract : Purpose of review: This article identifies research trends and synthesizes information from recent studies of avoidant personality disorder (AVPD). Recent findings: AVPD and social anxiety disorder (SAD) share genetic vulnerability, but may have distinct environmental risk factors that shape qualitative differences. Negative self-concept, shame proneness, and interpersonal hypersensitivity are characteristic of AVPD and may be predisposed to by heritable traits of high negative affectivity and low positive affectivity, and experiences of neglectful or emotionless parents. The interpersonal difficulties of AVPD may be associated with both anxious and avoidant attachment. Most individuals with AVPD do not also meet criteria for SAD. Summary: Integrative treatments incorporating cognitive behavioral strategies effective in SAD but also targeting shame aversion and avoidance may be most helpful for AVPD. Therapy adapted to both anxious attachment, associated with heightened interpersonal sensitivity and distress, and avoidant attachment, associated with experiential avoidance, may be optimal, though this is yet to be tested. Effective treatment of AVPD may enhance the outcome of comorbid conditions. More research is needed which compares three social anxiety groups (SAD alone, AVPD alone, and SAD plus AVPD) to further explore these disorders which are highly related, but which may have differences that are clinically relevant for individuals.